Pharmacological Treatment Options for Coronavirus Disease-19 in Renal Patients - null Jonny; Laurencia Violetta; Arief Sjamsulaksan Kartasasmita; Rully Marsis Amirullah Roesli; Coriejati Rita (International Journal of Nephrology)
Patients with chronic kidney disease (CKD), including dialysis and transplant patients, are at greater risk of contracting SARS-CoV-2 due to kidney dysfunction and preexisting comorbidities. To date, a specific guideline on managing these high-risk patients infected with COVID-19 has not been established. As the current management of COVID-19 comprises mainly experimental drugs, the authors aim to provide information on dosing adjustments at different stages of kidney dysfunction and notable renal side effects. We performed a nonsystematical review of currently available COVID-19 drugs exploring several different clinical trial databases and search browsers. Several antivirals and monoclonal antibodies used in COVID-19 treatment require dosage adjustments in kidney dysfunction. In a global pandemic setting, nephrologists need to consider the appropriate dosage according to the renal function and closely monitor the side effects of different drug combinations to obtain the optimum therapeutic effect while avoiding further renal damage. Further studies are required to determine the safety and efficacy of these drugs in renal patients.